Public Relations Associations as Trustworthy Partners. The APCE case study - Pereira, Sandra Cristina Martins (2021)
The purpose of this article is to present an ongoing study that seeks to know in what manner the affiliate members of the Portuguese Association for Corporate Communication (APCE) trust in the organization to defend their interests and to stimulate a rigorous path for the profession. Because there is a poor associative tradition in Portugal and many associations always struggled with lack of human resources and financing support, people normally did not take the associative work too serious. The associations would survive mostly with the help of a few strong headed volunteers that believed in their mission. But during the last decades both civic and professional associations have made an effort to assure a more formal structure with full-time and specialized employees which allow them to have a more active role in the society and with its affiliates. This is the case of APCE. So it would be great to find out what affiliate members now think of APCE and its commitment in establishing Corporate Communication and Public Relations as a critical success factor for companies. Despite being an autonomous non-profit driven entity, independent and active for almost 30 years, APCE has overcome a lot of obstacles and has undergone many restructurings that resulted from the rethinking of its mission. But one of its most difficult challenges over the years has been the capacity of gaining trust from practitioners and academics in the aptitude of APCE to represent them in their professional and research area. APCE board of directors is now interested in promoting a certification process for public relations, communication managers and strategists in Portugal. For several years it has struggled with a lack of recognition of both the value and competences of these practitioners. The ambition for an accreditation or certification of some kind is a long time expectation of many professionals and academics. So the main question is: Do affiliate members trust APCE to lead a process of certification or accreditation of PR in Portugal?